Influence of Cultural Factors on Pupil’s Transition from Primary to Secondary Schools in Laikipia West Sub-County, Kenya (International Journal of Scientific Research and Management (IJSRM), 2018)
From 2017, the government of Kenya aimed at attaining 100 percent transition rate of pupils from primary to secondary schools. In Laikipia West Sub-County whose primary schools are focused by the study, transition from primary to secondary schools averaged at 54.9% from 2008 to 2015. Cultural factors are highlighted in literature as to undermine transition of pupils from primary to secondary schools. The purpose of the study was to determine the extent to which cultural factors influence pupils’ transition from primary to secondary schools in Laikipia West Sub-county in Kenya. Using ex-post facto research design, data was collected using self-delivered questionnaire from a target population of 1064 respondents. The study was carried out on a randomly sampled population of 411 respondents, composed of 280 teachers and 131 PTA chairpersons in public primary schools in the area of study. Data was analyzed using simple regression at .05 alpha level. Findings from the study revealed that cultural factors were significantly influencing transition of pupils from primary to secondary schools (β= - .790) at 0.5 significance level. The study recommended that local leaders should organize for civic education in order to address the identified transition challenges so as to attain a 100% rate of progression to secondary schools.